Prispevek k poznavanju podzemnih gliv v Sloveniji - Piltaver, Andrej (Gozdarski vestnik, 2006)
The article presents the preliminary results of a recent inventory of hypogeous fungi. It gives insight into the previously poorly known hypogeous fungi in Slovenia and widens our knowledge of them. 35 taxa are listed, 29 from Slovenia. Most of the material (99 of 137 samples) is from Slovenia, the rest from neighbouring countries and some were obtained from the Far East. Special emphasis was put on truffles (Tuber) with 22 taxa. Among them 16 taxa are from Slovenia. These are: Tuber aestivum incl. T. uncinatum, T. borchii, T. brumale, T. brumale f. moschatum, T. hiemalbum, T. excavatum, T. excavatumvar. sulphureum, T. fulgens, T. macrosporum, T. magnatum, T. melanosporum, T. mesentericum, T. nitidum, Tuber puberulum, T. rufum and T. rufum sensu lato. Three Asian species, T. indicum, T. himalayense and T. pseudohimalayense, which come to the European market from the Far East are also presented. The tradition of truffles in Slovenia from the 18th century ismentioned. Their current status, compared to France, Italy and Croatia, is discussed and their potential role in sustainable development of rural areas is mentioned.
Keywords: glive; makromicete; gomoljke; Slovenia; Slovenija